ДІАЛОГІЧНА ВЗАЄМОДІЯ ЯК ЗАСІБ ВИРІШЕННЯ КОНФЛІКТІВ У ВНЗ (Педагогіка вищої та середньої школи, 2022)
The given article considers the concept npedagogical conflict” in a higher school, its negative and positive functions in pedagogical interaction are examined. The author of the article emphasizes the necessity of formation at the students of dialogical interaction skills as an original mean and purpose of the decision of the pedagogical conflict.